Ekspansi Politik Dinasti Jokowi: Peirce's Semiotic Study on the cover of Tempo Magazine - Fatiya Zahida; Nasution, Nadya Amalia (Universitas Muhammdiyah Yogyakarta, 2024)
Media coverage plays a crucial role in shaping public perception of political dynamics in Indonesia, particularly through visual representations. The increasing concerns about political dynasties and their impact on democratic processes have become a significant issue in Indonesian politics. This research applies Charles Sanders Peirce's semiotic theory to analyze the cover of Tempo magazine using qualitative research. The study aims to reveal the essential messages and ideological constructions conveyed to the audience by examining the signs, symbols, and meanings embedded in the cover design. The analysis focuses on the cover of Tempo magazine's 02 June 2023 edition,